Mapping exile and return : Palestinian dispossession and a political theology for a shared future - Weaver, Alain Epp (Fortress Press, 2014)
One of the most persistent, if vexing, issues facing not just theology but also political theory, sociology, and other disciplines, is the ongoing Palestinian-Israeli conflict. For theology, the problem is especially nettlesome on account of the church s shared history and tradition with Israel. Palestinians, including Palestinian Christians, bear the brunt of suffering and dispossession in the current situation, yet are burdened even more by Christian political appropriation of Zionism. Through an analysis of Palestinian refugee mapping practices for returning to their homeland, Alain Epp Weaver takes up the troubled issue of Palestinian dispossession and argues against the political theology embedded in Zionist cartographic practices that refuse and seek to eliminate evidence of co-existence. Instead, Alain Epp Weaver offers a political theology of redrawing the territory compatible with a bi-national vision for a shared Palestinian-Israeli future.